Assessing Acanthamoeba cytotoxicity: comparison of common cell viability assays - Loufouma Mbouaka, Alvie; Lesiak-Markowicz, Iwona; Heredero-Bermejo, Irene; Mazumdar, Rounik; Walochnik, Julia; Martín-Pérez, Tania (Frontiers in Microbiology, 2023)
Background In vitro models for studying interactions between Acanthamoeba and host cells are crucial for understanding the pathomechanism of Acanthamoeba and assessing differences between strains and cell types. The virulence of Acanthamoeba strains is usually assessed and monitored by using cell cytotoxicity assays. The aim of the present study was to evaluate and compare the most widely used cytotoxicity assays for their suitability to assess Acanthamoeba cytopathogenicity. Methods The viability of human corneal epithelial cells (HCECs) after co-culture with Acanthamoeba was evaluated in phase contrast microscopy. Results It was shown that Acanthamoeba is unable to considerably reduce the tetrazolium salt and the NanoLuc® Luciferase prosubstrate to formazan and the luciferase substrate, respectively. This incapacity helped to generate a cell density-dependent signal allowing to accurately quantify Acanthamoeba cytotoxicity. The lactate dehydrogenase (LDH) assay led to an underestimation of the cytotoxic effect of Acanthamoeba on HCECs since their co-incubation negatively affected the lactate dehydrogenase activity. Discussion Our findings demonstrate that cell-based assays using the aqueous soluble tetrazolium-formazan, and the NanoLuc® Luciferase prosubstrate products, in contrast to LDH, are excellent markers to monitor the interaction of Acanthamoeba with human cell lines and to determine and quantify effectively the cytotoxic effect induced by the amoebae. Furthermore, our data indicate that protease activity may have an impact on the outcome and thus the reliability of these tests.